Prevalence and Risk Factors for Anemia in Pregnant Women at Jaraga Sasameh Hospital - Jenri Sutrisno (Syntax Corporation Indonesia, 2023)
Information about incidence and risk factor for anemia is needed to help women avoid unwanted pregnancy outcome such as possibility of bleeding during labor and worse baby outcomes. The lack of data regarding the incidence of anemia in pregnant women in Barito Selatan Regency is still a major problem. The study was to describe the prevalence cases and to analyze the risk factor that cause anemia in pregnancy. The research method was analytic with a cross sectional design. The total sample of 235 pregnant women. Descriptive data analysis was presented in the distribution table and Chi-Square statistical test using SPSS version 26. The results showed anemia occurred in 164 of 235 respondents (69.8%). There was no significant relationship between number of pregnancies on the incidence of anemia (p>0.05). There was a significant relationship between maternal age, patient education, nutritional status, employment status, consumption of Fe, consumption of vitamin C and complication of pregnancy with the incidence of anemia (p<0.05). The conclusion of the study was that the factors associated with the incidence of anemia in pregnant women at Jaraga Sasameh Hospital were patient education, nutritional status, consumption of Fe, consumption of vitamin c and complication of pregnancy